Parásitos gastrointestinales de aves silvestres en un ecosistema ribereño urbano tropical en Heredia, Costa Rica - Pérez-Gómez, Gabriela; Jiménez-Rocha, Ana Eugenia; Bermúdez-Rojas, Tania (Revista de Biología Tropical, 2018)
Gastrointestinal parasites of wild birds in a tropical riverine urban ecosystem in Heredia, Costa Rica. In urban ecosystems, rivers provide various ecosystem services, among them, serving as interurban biological corridor, allowing birds to move and shelter in the middle of the city. However, high levels of pollution expose them, and even humans, to several health problems. Hence the importance of performing environmental diagnoses that allows to identify alterations and mitigate them in a timely manner. This study provides a first diagnosis of the parasitic situation of wild birds along the Pirro river which is located in an urban environment, fragmented and with high levels of surface water pollution. The sampling was carried out at the upper and middle part of the Pirro river in Heredia, Costa Rica. Mist-nets were used to capture the birds, and a general objective exam (GOE) was conducted in order to evaluate their nutritional and hydration state, as well as their physical state. In addition, stool samples were collected in order to characterize the gastrointestinal parasites (GPI). This procedure was carried out on 158 birds, belonging to 30 species, three PGI groups were identified: protozoa, nematodes and cestodes. The highest percentages of infection were represented by coccidia, with 97.6 %, followed by nematodes and cestodes with 2.4 %. Within the group of coccidios, it was possible to identify Eimeria spp., Isospora spp., in the nematodes: at the Strongylida group level and at the Capillaria spp., and for the cestodes: Choanotaenia spp. GOE resulted regular-to-good in all individuals captured, however, a general linear model was used to identify that the oral cavity and the state of the plumage could be the more linked variables with the percentage of infection by gastrointestinal parasites in birds, due to the fact that the oral cavity is the bird’s main route of ingestion, as well as the state of the plumage shows its vigor. Rev. Biol. Trop. 66(2): 788-798. Epub 2018 June 01.